2019
DOI: 10.24818/18423264/53.2.19.01
|View full text |Cite
|
Sign up to set email alerts
|

Using Gravity Model to Analyze Romanian Trade Flows between 2001 and 2015

Abstract: The main aim of the paper is to analyse the factors which influence the dimension, dispersion and the level of efficiency of Romania's trade flows in the 2001-2015 period. We have conducted a statistical analysis using EViews, which employed the Panel Least Squared method and the Estimated Generalized Least Squared method. We also provided a critical review of the literature covering the gravity model. Some of the questions we touch upon in this paper are: the variables for similarity as predictors of trade fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…These findings align with the study by Celebi [ 29 ] conducted across the low–income and high-income countries. Moreover, studies within the European region has underlined that the GDP and population levels are key contributors to export flows [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings align with the study by Celebi [ 29 ] conducted across the low–income and high-income countries. Moreover, studies within the European region has underlined that the GDP and population levels are key contributors to export flows [ 30 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from studies that resort to regression analysis, Miron et al . (2009), Ozturk et al . (2013), and Sanz-Villarroya (2005) embraced different methodological approaches to investigate the real convergence of some EEs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an attempt to test Romania's real convergence towards other Eastern European countries and the EU16 mean, Miron et al . (2009) resorted to the distances and clusters methodology and found that Romania was closer to Baltic countries, distanced from other neighbouring countries, and even more distanced from the Euro Area.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rault et al (2007) establish that the dimensions of the trade partner and the economic size positively affects the exports of Romania and Bulgaria in OECD countries. A recent study of Miron et al (2019) focused on Romania's exports during 2001-2015 period suggests that Romania's trade relationships are concentrated on the neighbouring countries, sharing a common border, with similar GDP per capita and population levels.…”
Section: Literature Reviewmentioning
confidence: 99%